1997
DOI: 10.1023/a:1018476414781
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The objective of this study was to examine the effects of the intake of dietary fat upon colorectal cancer risk in a combined analysis of data from 13 case-control studies previously conducted in populations with differing colorectal cancer rates and dietary practices. Original data records for 5,287 cases of colorectal cancer and 10,470 controls were combined. Logistic regression analysis was used to estimate odds ratios (OR) for intakes of total energy, total fat and its components, and cholesterol. Positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…However, elevated insulin levels may also increase hepatic GH receptor (open bar) number and activity, reflected by increases in levels of circulating growth hormone-binding protein (GHBP). This effect may lead to a rise in GH-regulated hepatic IGF-I and IGFBP-3 production, with a greater increase in levels of circulating IGF-I relative to IGFBP-3 (Sandhu et al, 2002) Diet and cancer preventionColorectal adenomas and cancer have not generally been related to fat consumption in case-control (Howe et al, 1997), prospective (Giovannucci and Goldin, 1997;Potter, 1999) or intervention studies . Prospective cohort studies of breast cancer have likewise not supported a role of dietary fat, as was suggested in ecologic and some case-control studies (Smith-Warner et al, 2001a;Kushi and Giovannucci, 2002).…”
Section: Fatmentioning
confidence: 99%
“…However, elevated insulin levels may also increase hepatic GH receptor (open bar) number and activity, reflected by increases in levels of circulating growth hormone-binding protein (GHBP). This effect may lead to a rise in GH-regulated hepatic IGF-I and IGFBP-3 production, with a greater increase in levels of circulating IGF-I relative to IGFBP-3 (Sandhu et al, 2002) Diet and cancer preventionColorectal adenomas and cancer have not generally been related to fat consumption in case-control (Howe et al, 1997), prospective (Giovannucci and Goldin, 1997;Potter, 1999) or intervention studies . Prospective cohort studies of breast cancer have likewise not supported a role of dietary fat, as was suggested in ecologic and some case-control studies (Smith-Warner et al, 2001a;Kushi and Giovannucci, 2002).…”
Section: Fatmentioning
confidence: 99%
“…There are associations between oral and esophageal cancers and high intake of alcohol, tobacco, and of scalding hot food or drinks [156]. Colon cancer risk appears to be worsened by high intake of red meat, salt-preserved meat, and fat, although the data is not completely conclusive [157-159]. Excessive intake of alcohol is associated with cirrhosis-induced liver cancer and is a risk factor for breast cancer [149,160].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a matched case-control study of colon and rectal cancer in Chinese Americans located in North America showed an OR of 1.8 (CI 1.3–2.5) for males and 2.0 (CI 1.2–3.5) for females from saturated fat (Whittemore et al 1990). In contrast, a combined analysis of 13 case-control studies did not observe any associations with total fat or fat constituents (Howe et al 1997). Among cohort studies, both positive (Giovannucci et al 1994; Willett et al 1990) and null (Lin et al 2004; Dahm et al 2010; Sun et al 2012) associations of total fat and colon cancer have been reported.…”
Section: Discussionmentioning
confidence: 95%
“…A pooled analysis of 13 case-control studies found no evidence of any energy-independent effects of total fat and colorectal cancer risk (Howe et al 1997). In a meta-analysis of 6 prospective cohort studies on the relationship between animal fat consumption and colorectal cancer (Alexander et al 2009), four observed null associations (Bostick et al 1994; Goldbohm et al 1994; Lin et al 2004; Sanjoaquin et al 2004) and two reported elevated risk with increased animal fat intake (Giovannucci et al 1994; Willett et al 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation